Performance of Sequential Organ Failure Assessment and Simplified Acute Physiology Score II for Post-Cardiac Surgery Patients in Intensive Care Unit - Xu, Fei; Li, Weina; Zhang, Cheng; Cao, Rong (Frontiers in Cardiovascular Medicine, 2021)
Background: The aim of study is to assess the performance of sequential organ failure assessment score (SOFA) and simplified acute physiology score (SAPS II) on outcomes of patients with cardiac surgery and identify the cut-off values to provide reference for early intervention. Methods: All data were extracted from MIMIC-III (Medical Information Mart for Intensive Care-III) database. Cut-off values were calculated by receiver operating characteristic curve and Youden indexes. Patients were grouped respectively according to the cut-off values of SOFA and SAPS II. Non-adjust model and adjust model were established to evaluate prediction of risk. Comparison of clinical efficacy between two scoring systems was conducted by decision curve analysis (DCA). The primary outcomes of this study were in-hospital mortality, 28-day mortality, 90-day mortality and one-year mortality after cardiac surgery. The secondary outcomes included length of hospital stay and intensive care unit (ICU) stay, the incidence of acute kidney injury (AKI) within 7 days after ICU admission. Results: A total of 6122 patients were collected and divided into H-SOFA group (SOFA≥7) and L-SOFA group (SOFA<7) or H-SAPS II group (SAPS II ≥43) and L-SAPS II group (SAPS II <43). In-hospital mortality, 28-day mortality, 90-day mortality and one-year mortality were higher, the length of hospital and ICU stay were longer in H-SOFA group than L-SOFA group (p<0.05), while the incidence of AKI was not significantly different. In-hospital mortality, 28-day mortality, 90-day mortality, one-year mortality and the incidence of AKI were all significantly higher in H-SAPS II group than L-SAPS II group (p<0.05). Hospital stay, ICU stay were longer in H-SAPS II group than L-SAPS II group (p<0.05). According to DCA, SAPS II scoring system had more net benefits on prognosing long term mortality compared with SOFA scoring system. Conclusion: Exceeding the cut-off values of SOFA and SAPS II score could lead to increased mortality and extended length of ICU and hospital stay. The SAPS II scoring system had a better discriminative performance of 90-day mortality and one-year mortality in post-cardiac surgery patients than SOFA scoring system. Emphasizing the critical value of scoring system is of significance for timely treatment.